STUDENTS AND TEACHERS’ PERCEPTIONS TOWARDS THE USE OF ONLINE TEACHING AS AN ALTERNATIVE DELIVERY MODE (ADM) - Cutillas, AL; Hermosisima, MC (Proceedings of the International Conference on Education, 2023)
Abstract This study explores the lived experiences of students and teachers at Santa Fe National High School in Cebu, Philippines, during the COVID-19 pandemic, specifically focusing on the implementation of online modular learning. The study aims to identify the technological platforms used, their role in the current learning modality, and the challenges teachers and students encounter. Employing a transcendental phenomenological design and using Key Informant Interviews (KII) for data collection, the study utilized qualitative data analysis frameworks by Moustakas (1994) and a deductive thematic analysis approach for data interpretation and coding. The findings suggest that technology played a significant role in teaching and learning, providing students with the ability to mitigate struggles and enhance human and social capabilities, positively impacting their well-being. Teachers perceived the alternative delivery mode (ADM) as significantly impacting the current educational setting, indicating that education is a two-way process that requires readiness and satisfaction. Based on the results, students and teachers believe that online teaching is a viable framework that enhances learning continuity, aligning with the Department of Education’s vision to continue the teaching and learning process despite the pandemic.